PATTERNS OF SILVER HOARDING IN MIDDLE ROMAN PALESTINE: AD 73-300 - Joshua Goldman (Journal of Ancient History and Archaeology)
Middle Roman Palestine encompasses the period between the end of the First Jewish Revolt in AD 70-73 and the Christianisation of Palestine in the early fourth century. The greatest concentration of hoards from this phase was during the Second Jewish Revolt (Bar Kokhba Revolt) between AD 132 and 135/136, providing a wealth of information about precious metal hoarding patterns, especially during periods of conflict. The Crisis of the Third Century also influenced hoarding patterns in Palestine, potentially illustrating a causation between enacted monetary reforms and reactionary increases in hoarding. Additional topics that will be explored within this hoard evidence include denominations of silver coins, reigns and mints represented, and quantities of hoards and coins. These facets will illuminate aspects of silver hoarding in second- and third-century Palestine.